Inhalable Microparticulate System for Tuberculosis: An Updated Review - T, Mallamma; Goudanavar, Prakash (Indian Journal of Pharmaceutical Education and Research, 2023)
Antibiotic efficiency declines in TB treatment and bacteria develop resistance over time due to numerous barriers such as lung mucus and biofilms surrounding the microbe. To tackle drug-resistant tuberculosis, there is a critical need for the discovery of novel medications and the repurposing of existing drugs with new mechanisms of action. Despite these challenges Vascular drug delivery shows promise as a potential treatment option for tuberculosis due to its ability to achieve high medicine levels at the infection site with reducing toxicities. The inhalable antitubercular Microparticles (MP) are directly bound in a thick mucin mess network in the lungs, that allows for high concentrations at the site of action while limiting systemic distribution, resulting in more effective therapy with lower required doses, side effects and rapid elimination by mucociliary clearance. there are several challenges in obtaining a such formulation to meets all of the criteria for physico-chemical, aerodynamic, and biological properties, which is why only a small number of the investigated systems can reach the clinical trial phase and proceed to everyday use. The current study focuses on methods to create inhalable Microparticles for antitubercular drug delivery systems by using different carriers to the lungs, stressing how drug bioavailability, Drug Deposition might be affected by the route of administration. Additionally, the advantages and disadvantages of the novel distribution techniques and Evaluation parameters are explored.
Keywords: Mycobacterium tuberculosis (MTB); Inhalable Microparticles (MP); Multidrug-Resistant Tuberculosis (MDR-TB); Aspect Ratio (AR); Metered Dose Inhalers (MDI)